TOWARDS AN EVOLUTIONARY ECONOMIC THEORY - DINGA Emil (Management of Sustainable Development)
Today, the neoclassic economic theory still dominates the economic analysis, prediction, and even public economic policy, encouraged, unfortunately, by the career criteria in science and education fields. In such a context, the objectives of the paper are: (1) to systematize the findings related to the unrealism and theoretical and methodological mistakes of the economic neoclassic model; (2) to argue about the desirability, reliability, realism, and efficaciousness of an evolutionary model of the economy (and of Economics); (3) to draw the basic lines which an evolutionary economic theory could be edified on, starting from both the statu quo in the matter and the logical examination of the question. The approach of research is a mix between logical and historical (but not empirical) views regarding the evolutionary economic model/theory. The main results are: (a) arguing on the possibility of crystalizing the basic concepts of an evolutionary economic model; (b) making proposals for the evolutionary economic mechanism (in its abstract understanding – as cybernetic system of order 3); (c) warning on the risks of a tale quale taking over of the evolutionary concepts from Biology; (d) identifying the principles to be followed in building up of an evolutionary economic theory.